WNT regulation of embryonic development likely involves pathways independent of nuclear CTNNB1. Issue 4 (April 2017) - Tribulo, Paula; Moss, James I; Ozawa, Manabu; Jiang, Zongliang; Tian, Xiuchun (Cindy); Hansen, Peter J
Abstract : The bovine was used to examine the potential for WNT signaling to affect the preimplantation embryo. Expression of seven key genes involved in canonical WNT signaling declined to a nadir at the morula or blastocyst stage. Expression of 80 genes associated with WNT signaling in the morula and inner cell mass (ICM) and trophectoderm (TE) of the blastocyst was also evaluated. Many genes associated with WNT signaling were characterized by low transcript abundance. Seven genes were different between ICM and TE, and all of them were overexpressed in TE as compared to ICM, including WNT6, FZD1, FZD7, LRP6, PORCN, APC and SFRP1 . Immunoreactive CTNNB1 was localized primarily to the plasma membrane at all stages examined from the 2-cell to blastocyst stages of development. Strikingly, neither CTNNB1 nor non-phospho (i.e., active) CTNNB1 was observed in the nucleus of blastomeres at any stage of development even after the addition of WNT activators to culture. In contrast, CTNNB1 associated with the plasma membrane was increased by activators of WNT signaling. The planar cell polarity pathway (PCP) could be activated in the embryo as indicated by an experiment demonstrating an increase in phospho-JNK in the nucleus of blastocysts treated with the non-canonical WNT11. Furthermore, WNT11 improved development to the blastocyst stage. In conclusion, canonical WNT signaling is attenuated in the preimplantation bovine embryo but WNT can activate the PCP component JNK. Thus, regulation of embryonic development by WNT is likely to involve activation of pathways independent of nuclear actions of CTNNB1.